2010
DOI: 10.3897/compcytogen.v4i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Geographical distribution of the cryptic species Agrodiaetus alcestis alcestis, A. alcestis karacetinae and A. demavendi (Lepidoptera: Lycaenidae) revealed by cytogenetic analysis

Abstract: Abstract. Agrodiaetus alcestis (Zerny, 1932) and A. demavendi (Pfeiffer, 1938) belong to the "brown" complex of the genus Agrodiaetus Hübner, 1822. This complex includes several cryptic species which are extremely uniform in wing colouration and genitalia structure, but have distinct chromosome numbers. In this paper we analyse karyotypes of A. alcestis karacetinae Lukhtanov et Dantchenko, 2002 and A. demavendi in populations from Iran. We demonstrate that A. alcestis karacetinae and A. demavendi are sympat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Sequences were aligned using the BioEdit software (Hall 1999) and edited manually. Phylogenetic hypotheses were inferred using Bayesian inference as described previously (Vershinina and Lukhtanov 2010, Lukhtanov et al 2016a, b). Briefly, the Bayesian analysis was performed using the program MrBayes 3.2 (Ronquist et al 2012) with default settings as suggested by Mesquite (Maddison and Maddison 2015): burn-in=0.25, nst=6 (GTR + I + G).…”
Section: Methodsmentioning
confidence: 99%
“…Sequences were aligned using the BioEdit software (Hall 1999) and edited manually. Phylogenetic hypotheses were inferred using Bayesian inference as described previously (Vershinina and Lukhtanov 2010, Lukhtanov et al 2016a, b). Briefly, the Bayesian analysis was performed using the program MrBayes 3.2 (Ronquist et al 2012) with default settings as suggested by Mesquite (Maddison and Maddison 2015): burn-in=0.25, nst=6 (GTR + I + G).…”
Section: Methodsmentioning
confidence: 99%
“…This transpalearctic species has been known to have a stable karyotype (n=90, including one large, one medium and 88 small elements) throughout its whole distribution range from Spain in the west to the Altai in the east (de Lesse 1960a,b, Kandul 1997, Lukhtanov and Datchenko 2002, Vila et al 2010, Vershinina and Lukhtanov 2010, Przybyłowicz et al 2014). The number n=90 was also found in Polyommatus ripartii pelopi (Coutsis et al 1999), and we confirmed this count for samples from South and Central Greece and from Bulgaria.…”
Section: Chromosomal Diversitymentioning
confidence: 99%
“…Mean uncorrected p-distances between haplogroups were calculated in MEGA7 (Kumar et al 2015). Phylogenetic hypotheses were inferred using Bayesian inference (BI) as described previously (Vershinina and Lukhtanov 2010, Talavera et al 2013a,b). Briefly, Bayesian analyses were performed using the program MrBayes 3.1.2 (Huelsenbeck and Ronquist 2001) with default settings as suggested by Mesquite (Maddison and Maddison 2015): burn-in=0.25, nst=6 (GTR + I +G).…”
Section: Methodsmentioning
confidence: 99%